Espacios públicos: Estado - sociedad, distancias y proximidades. - Cardeña Dios, Estela (2005)
The present text approaches the subject of the Public Space emphasizing the relations State Society, from a theoretical revision of its different perspective and interpretations. In this sense, it presents the sprouting of the public space, his transformations and perspective in the classic and contemporary tradition, as well as, its types and dimensions.